Mary-Kate and Ashley Olsen - Fitzgerald, Stephanie (Chicago : Raintree, 2006)
Presents a short biography of Mary Kate and Ashley Olsen, and chronicles their childhood and entrance into show business at the age of nine months, later film roles, their family, and more.
Includes bibliographical references (p. 44), filmography (p. 44), and index.
5.5
5-8
Keywords: Olsen, Ashley, -- 1986- -- Juvenile literature; Olsen, Mary-Kate, -- 1986- -- Juvenile literature; Olsen, Ashley, -- 1986-; Olsen, Mary-Kate, -- 1986-; Olsen, Ashley, -- 1986-; Olsen, Mary-Kate, -- 1986-; Actors -- United States -- Biography -- Juvenile literature; Actors and actresses; Actors -- United States -- Biography